An organizational entrepreneurship model based on organizational learning: a systematic review study from Iran Health Insurance Organization - Shahrzad Inanloo; Ali Mehdizadeh Ashrafi; Majid Jahangirfard (Shahid Beheshti University of Medical Sciences, 2023)
Background: One of the most basic tools and strategies for developing new ideas and entrepreneurship is establishing the entrepreneurial culture in the organization. The present study explained and analyzed the dimensions and components of organizational entrepreneurship based on organizational learning. Methods: The approach of this study was qualitative and was carried out with the seven-step hybrid method. Systematically analyzed the results of previous studies. According to the depth of the study in this approach, the range of scientific articles and documents is less than 70 cases. To achieve the basic framework of the research based on the seven-step method of Sandelowski. Results: The concept of organizational entrepreneurship based on organizational learning was identified and classified into 6 components, 16 dimensions, and 159 indicators. The components included causal, contextual, intervening factors, axial phenomenon, strategies, and implications of organizational entrepreneurship based on organizational learning. The causal conditions included indicators of organizational performance, competitive advantage, organizational change, strategic leadership, and individual factors of organizational learning. Contextual factors included organizational environment and organizational infrastructure. Conclusion: Entrepreneurship is a tool to create jobs and generate wealth. Entrepreneurial activities in the organization can be considered innovative actions guided through an organized system of human relations and a combination of resources to achieve a specific goal. If organizational entrepreneurship is implemented with an organizational learning approach, it can play a very effective role in improving the organization's performance and achieving goals.